Impact of Working Capital Management on Profitability of Non-Financial Firms - Khadka, Srijana; Khadka, Ajaya Kumar (KMC Research Journal, 2022)
The managers of today’s non-financial enterprises are more concerned with working capital management. This study used a descriptive and comparative causal research approach to examine working capital management’s effect on profitability. Regression and correlation test was performed for 15 observations from three non-financial institutions based on a purposive sample design. The result shows a strong positive correlation between the current ratio (CR) and returns on assets (ROA), cash conversion cycle (CCC), receivable conversion period (RCP), and payable deferral period (PDP) have no significant correlation. Regression results show that CR, PDP, and CCC are significant predictors of ROA, and RCP has no significant effect. It is recommended that non-financial managers focus on maintaining a favorable current ratio while reducing the cash conversion cycle and optimizing payment periods. By doing so, they can improve their firm’s liquidity position, effectively manage cash flow, and ultimately enhance profitability.